Efektivitas Penggunaan Pupuk Hayati (Enterobacter cloacae) untuk Meningkatkan Hasil dan Mutu Benih Padi Varietas Cigeulis - NI NYOMAN DIAH UTTARI; I DEWA NYOMAN NYANA; ANAK AGUNG MADE ASTININGSIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT Biological Fertilizer Usage Effectiveness (Enterobacter cloacae) to Increase Yield and Quality of Rice Seeds Varieties Cigeulis The purposes of this research were to find out the influence of biological fertilizer Egary which contains rhizobacteria Enterobacter cloacae related to the crop of Cigeulis rice, as well as to test the effectiveness of biological fertilizer to reduce the utilization of chemical fertilizer, and to obtain the quality of the seed production. The resullt indicated that the augmentation of biological fertilizer plus chemical fertilizer phonska and urea at 100 kg/ha each (Py) increased the production of the rice crop about 1.8 tons/ha or increased about 33.93% and the result of biological fertilizer plus chemical fertilizer phonska and urea at 200 kg/ha each (Pz) increased about 0.8 tons/ha or about 33.13% if compared with control. The research of Py treatment with biological fertilizer plus chemical fertilizer phonska and urea at 100 kg/ha each, produced Cigeulis rice crop variety for 6.3 tons/ha and improved the quality of the seeds both physical and physiological parameters, produced 1000 grain weight of seeds, germination and vigor highest power savings and has better endurance than Pz and control (30.28 g, 89.11%, and 85.89%, respectively). Keywords: Fertilizer, seeds, yield